2012
DOI: 10.5483/bmbrep.2012.45.12.240
|View full text |Cite
|
Sign up to set email alerts
|

Structure and catalytic mechanism of human protein tyrosine phosphatome

Abstract: Together with protein tyrosine kinases (PTKs), protein tyrosine phosphatases (PTPs) serve as hallmarks in cellular signal transduction by controlling the reversible phosphorylation of their substrates. The human genome is estimated to encode more than 100 PTPs, which can be divided into eleven sub-groups according to their structural and functional characteristics. All the crystal structures of catalytic domains of sub-groups have been elucidated, enabling us to understand their precise catalytic mechanism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 55 publications
(59 reference statements)
1
16
0
Order By: Relevance
“…Such clas sification is confirmed with the results of experimental genomics [6]. Some protein phosphatases that were determined as serine/threonine specific, are able to dephosphorylate tyrosine residues [1,7,8]. Besides, it was found that certain animal phosphatases with dual specificity are able to dephosphorylate proteins on cysteine, arginine, lysine, asparagine, histidine, and glutamic acid residues [1,[9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 70%
“…Such clas sification is confirmed with the results of experimental genomics [6]. Some protein phosphatases that were determined as serine/threonine specific, are able to dephosphorylate tyrosine residues [1,7,8]. Besides, it was found that certain animal phosphatases with dual specificity are able to dephosphorylate proteins on cysteine, arginine, lysine, asparagine, histidine, and glutamic acid residues [1,[9][10][11][12][13].…”
Section: Introductionsupporting
confidence: 70%
“…The presence of the thiophosphate bond was further confirmed by stability to hydroxylamine and lability to iodine‐treatment, all of which serve to differentiate thiophosphates from acylphosphates . A mechanism was proposed whereby the active site cysteine nucleophilically attacks the phosphorus atom of the phosphotyrosine to generate the pCys‐intermediate, which is then subject to hydrolysis by water . This cysteine‐dependent hydrolysis mechanism is now generally accepted and although transient, the pCys on PTPs are known to exist long enough to facilitate detection by gel‐based methods…”
Section: Cysteine Phosphorylationmentioning
confidence: 99%
“…This observation suggests that the new complex could have some selectivity towards specific CBPs compared to others, inhibiting better phosphatases with a large catalytic pocket (e.g. PTEN), 33 or interacting with specific secondary substrate binding sites (e.g. in the case of SHP2 and LMW-PTP).…”
Section: Synthesis Of the Trifunctional Optical Probementioning
confidence: 99%